Advanced glycation endproducts interfere with integrin-mediated osteoblastic attachment to a type-I collagen matrix - McCarthy, Antonio Desmond (2004)
The adhesion of osteoblasts to bone extracellular matrix, of which type-I collagen constitutes >85%, can modulate diverse aspects of their physiology such as growth, differentiation and mineralisation. In this study we examined the adhesion of UMR106 rat osteoblast-like cells either to a control (Col) or advanced-glycation-endproduct-modified (AGEs-Col) type I collagen matrix. We investigated the possible role of different integrin receptors in osteoblastic adhesion, by co-incubating these cells either with β-peptide (conserved sequence 113-125 of the β subunit of integrins) or with two other peptides, RGD (Arg-Gly-Asp) and DGEA (Asp-Gly-Glu-Ala), which are recognition sequences for the α-subunits of α1,5β1 and α2β1 integrins. Collagen glycation inhibited the adhesion of UMR106 osteoblasts to the matrix (40% reduction versus Col, P<0.001). β-Peptide showed a dose- and glycation-dependent inhibitory effect on adhesion, and at a concentration of 100μM decreased the attachment of UMR106 cells to both matrices (42% to Col, P<0.001; and 25% to AGEs-Col, P<0.01). The synthetic peptides RGD (1mM) and DGEA (5mM) inhibited the attachment of UMR106 cells to Col (30 and 20%, P<0.01 and P<0.001, respectively), but not to AGEs-Col. β-Peptide induced an increase in UMR106 cell clumping and a decrease in cellular spreading, while DGEA increased spreading with cellular extensions in multiple directions. These results indicate that both α and β integrin subunits participate in osteoblastic attachment to type-I collagen, probably through the α 1,5β1 and α2β1 integrins. AGEs-modification of type-I collagen impairs the integrin-mediated adhesion of osteoblastic cells to the matrix, and could thus contribute to the pathogenesis of diabetic osteopenia.